PENGARUH MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP MOTIVASI BELAJAR SISWA KELAS IV DI SD NEGERI 060841 MEDAN - Waruwu, Yolanda Aristina; Juliana; Ester Julinda Simarmata; Eka Margaretha Sinaga; Irmina Pinem; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the cooperative learning model of the Student Achievement Division (STAD) type on the learning motivation of fourth-grade students at SD Negeri 060841 Medan Petisah in the 2024/2025 academic year. This research employed a quantitative approach. The population of the study consisted of all students from grades I to VI at SD Negeri 060841 Medan Petisah, totaling 174 students. The sample was selected using a purposive sampling technique, with 23 fourth-grade students serving as the research sample. The results of the study indicated a correlation coefficient of 0.669, meaning that rcalculated ​ (0.669) ≥ rtable ​ (0.433); therefore, the alternative hypothesis (Ha) was accepted. This result shows a very strong effect of the cooperative learning model of the Student Achievement Division (STAD) type on the learning motivation of fourth-grade students at SD Negeri 060841 Medan Petisah. Furthermore, the t-test results showed that tcalculated ​ ≥ ttable ​, namely 4.120 ≥ 2.069, confirming that Ha was accepted. Thus, it can be concluded that there is a positive and significant effect of the cooperative learning model of the Student Achievement Division (STAD) type on the learning motivation of fourth-grade students at SD Negeri 060841 Medan Petisah in the 2024/2025 academic year.